High-temperature-resistant hydrophobic anticorrosive coating as well as preparation method and application thereof
By introducing hydrophobically modified ZIF-67@MgAlCeFe-LDH and 2-benzothiazolethiosuccinic acid into the epoxy resin coating, a high-temperature hydrophobic anti-corrosion coating was prepared, which solved the problems of high brittleness and insufficient hydrophobic performance of epoxy resin coating at high temperatures, and achieved excellent corrosion resistance.
Patent Information
- Application Number
- CN202510505439.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-22
- Publication Date
- 2025-07-25
- Estimated Expiration
- 2045-04-22
AI Technical Summary
Existing epoxy resin coatings are highly brittle at high temperatures, and the release of solvents leads to microporous defects, affecting corrosion resistance and hardness, and insufficient hydrophobic properties, making it difficult to effectively prevent metal corrosion.
The modified ZIF-67@MgAlCeFe-LDH was used in conjunction with 2-benzothiazolethiosuccinic acid to prepare modified ZIF-67@MgAlCeFe-LDH through hydrothermal reaction, and mixed with epoxy resin, filler, dispersant, defoaming agent, film additive and curing agent to form a high-temperature hydrophobic and anti-corrosion coating.
It significantly improves the corrosion resistance and hydrophobic properties of the coating, can effectively prevent metal corrosion at high temperatures, and has excellent corrosion resistance.
Smart Images

Figure BDA0005369656680000091
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of anti-corrosion coatings. More specifically, it relates to a high-temperature resistant hydrophobic anti-corrosion coating, its preparation method and application. Background Art
[0002] The corrosion of metal materials will cause huge economic losses and many potential safety hazards. At present, combined measures of anti-corrosion coatings and cathodic protection are generally adopted at home and abroad to protect the corrosion of buried or deep-sea steel pipelines. Epoxy resin coatings are composed of base materials such as epoxy resin, curing agents, pigment fillers, solvents and various functional additives. Epoxy resin coatings usually have strong corrosion protection performance, good electrical insulation, high strength and good chemical properties, such as chemical resistance, oil resistance and alkali resistance. At the same time, epoxy resin coatings also have process advantages such as strong adhesion and can be operated at room temperature, and excellent physical and mechanical properties. However, the network structure formed by cross-linking and curing will also cause epoxy resin coatings to show a certain degree of brittleness macroscopically. In addition, the solvent dissolved in the resin will be released during curing, generating microporous defects on the coating, providing a channel for the corrosion medium to reach the substrate, and affecting the corrosion resistance and hardness of the coating.
[0003] CN118995000A discloses a preparation method of a fluorinated graphene / epoxy resin composite anti-corrosion coating. Using GO as the initial raw material, HF generated by the metathesis reaction of sulfuric acid (H2SO4) and lithium fluoride (LiF) is used as the fluorination reagent, and fluorination reaction is carried out for 12 h in a hydrothermal environment at 180 °C to obtain FG. And the microstructure and morphology of the prepared FG are analyzed by characterization methods such as FT-IR. Subsequently, the surface wettability, friction resistance, corrosion resistance and water resistance of the fluorinated graphene / epoxy resin composite anti-corrosion coating are characterized by static contact angle analysis. After various structural and performance characterizations, the FG prepared by this method has hydrophobicity and wear resistance, and can be evenly dispersed in the epoxy resin matrix, effectively enhancing the water absorption resistance, friction resistance and corrosion resistance of the epoxy resin coating.
[0004] CN118995011A discloses a high-temperature resistant superhydrophobic long-lasting anti-corrosion coating and its preparation method. The preparation method of the high-temperature resistant superhydrophobic long-lasting anti-corrosion coating uses γ-methacryloxypropyltrimethoxysilane to modify the surface of nanoparticles to obtain modified nanoparticles; uses vinyltrimethoxysilane to modify the surface of nano-silica to obtain superhydrophobic silica; polymerizes the modified nanoparticles, superhydrophobic silica and methacrylic acid, and then grafts them onto phenolic epoxy resin through a ring-opening reaction to obtain modified epoxy vinyl resin; mixes the modified epoxy vinyl resin and a curing agent evenly and sprays them onto the surface of a metal substrate, and after curing, a high-temperature resistant superhydrophobic long-lasting anti-corrosion coating is obtained. The present invention not only improves the crosslinking degree, heat resistance, shielding property and toughness of epoxy vinyl resin, but also improves the hydrophobicity of the coating, making the coating have long-lasting anti-corrosion property.
[0005] CN118852947A discloses a preparation method of a superhydrophobic anti-corrosion coating with dual dynamic covalent bonds. It includes the following steps: First, apply a silane coupling agent to graft dynamic disulfide bonds on the surfaces of graphene and carbon nanotubes, mix them with ethanol and a fluorinated modifier to construct modified graphene and carbon nanotubes containing dynamic disulfide bonds; prepare anti-corrosion coating component A through epoxy resin stock solution, organic solvent and graphene containing dynamic disulfide bonds, and prepare anti-corrosion coating component B by adding modified carbon nanotubes to a curing agent containing dynamic ester bonds; finally, mix anti-corrosion coating component A and anti-corrosion coating component B to prepare a superhydrophobic anti-icing coating with self-healing function. The present invention constructs dynamic disulfide bonds on the surfaces of graphene and carbon nanotubes, and selects a curing agent containing dynamic ester bonds to cure the coating to prepare a superhydrophobic anti-corrosion coating with excellent self-healing and recyclable properties.
[0006] CN118165613A discloses a hydrophobic modified anti-corrosion coating and its preparation method. The method for preparing the hydrophobic modified anti-corrosion coating includes: soaking the anti-corrosion coating in a PDMS homogeneous solution, standing, and curing to obtain the hydrophobic modified anti-corrosion coating. The preparation of the anti-corrosion coating includes: scraping and drying the coating, and curing to obtain the anti-corrosion coating. Among them, the preparation method of the coating includes: etching g-C3N4 in an acidic solution and ultrasonicating to obtain etched g-C3N4; mixing the etched g-C3N4, aniline and water, adjusting the pH to obtain a polyaniline precursor solution with a pH of 1-4, subjecting the polyaniline precursor solution to a photopolymerization reaction to obtain a second precipitate, washing, and freeze-drying to obtain a polyaniline composite nanomaterial; dispersing the polyaniline composite nanomaterial in waterborne epoxy resin, first stirring and then ultrasonicating to obtain a first solution, and mixing the first solution and a curing agent evenly to obtain the coating. The hydrophobic modified anti-corrosion coating of the present invention has the advantages of anti-corrosion, anti-ultraviolet, anti-algae, high hydrophobicity and long lifespan.
[0007] By adding hydrophobic additives to the coating or spraying on the coating surface, etc., the hydrophobic material can also achieve hydrophobic performance, thereby blocking moisture erosion and avoiding metal corrosion. Based on this, the present invention provides an anti-corrosion coating with excellent hydrophobic and corrosion-resistant properties and the like. Summary of the Invention
[0008] The technical problem to be solved by the present invention is to overcome the defects and deficiencies of the prior art and provide a high-temperature resistant hydrophobic anti-corrosion coating, its preparation method and application. A high-temperature resistant hydrophobic anti-corrosion coating provided by the present invention, by weight, the raw materials of the coating include the following components: 100-140 parts of epoxy resin; 3-7 parts of 2-benzothiazolethiosuccinic acid; 2-6 parts of hydrophobic modified ZIF-67@MgAlCeFe-LDH; 4-8 parts of filler; 2-6 parts of dispersant; 1-3 parts of defoamer; 2-4 parts of film assistant; 15-35 parts of curing agent; 20-30 parts of water; 10-20 parts of ethanol. By adding hydrophobic modified ZIF-67@MgAlCeFe-LDH, the hydrophobic performance of the coating can be improved, and in combination with 2-benzothiazolethiosuccinic acid, the corrosion resistance of the anti-corrosion coating is significantly improved by using the interaction between the two. That is, the anti-corrosion coating prepared by the present invention has excellent corrosion resistance, hydrophobic performance and high-temperature resistance.
[0009] The purpose of the present invention is to provide a high-temperature resistant hydrophobic anti-corrosion coating.
[0010] Another purpose of the present invention is to provide a preparation method of a high-temperature resistant hydrophobic anti-corrosion coating.
[0011] Another purpose of the present invention is to provide an application of a high-temperature resistant hydrophobic anti-corrosion coating in the field of anti-corrosion.
[0012] The above purposes of the present invention are achieved by the following technical solutions:
[0013] A high-temperature resistant hydrophobic anti-corrosion coating, by weight, the raw materials of the coating include the following components:
[0014] 100-140 parts of epoxy resin;
[0015] 3-7 parts of 2-benzothiazolethiosuccinic acid;
[0016] 2-6 parts of hydrophobic modified ZIF-67@MgAlCeFe-LDH;
[0017] 4-8 parts of filler;
[0018] 2-6 parts of dispersant;
[0019] 1-3 parts of defoamer;
[0020] 2-4 parts of film assistant;
[0021] 15 - 35 parts of curing agent;
[0022] 20 - 30 parts of water;
[0023] 10 - 20 parts of ethanol.
[0024] In the present invention, in a preferred technical solution, the preparation method of the hydrophobic modified ZIF-67@MgAlCeFe-LDH comprises the following steps:
[0025] (1) Weigh magnesium salts, cerium salts, iron salts and aluminum salts, dissolve them in water to form a mixed salt solution, stir, then add an alkali solution until the pH of the solution is 9 - 11, then transfer it to a hydrothermal reaction kettle for hydrothermal reaction, centrifuge, wash, and dry to obtain MgAlCeFe-LDH;
[0026] (2) Disperse the MgAlCeFe-LDH obtained in step (1) and cobalt salts into ethanol water, stir, then add dimethylimidazole, stir at 50 - 70 °C for 2 - 4 h, let it stand for 4 - 8 h, filter, wash, and dry to obtain ZIF-67@MgAlCeFe-LDH;
[0027] (3) Ultrasonically disperse the ZIF-67@MgAlCeFe-LDH obtained in step (2) and fluorodecyltriethoxysilane into ethanol, stir at 55 - 75 °C for 2 - 4 h, filter, wash, and dry to obtain the hydrophobic modified ZIF-67@MgAlCeFe-LDH.
[0028] Further, in step (1), the magnesium salt is at least one of magnesium nitrate, magnesium acetate, and magnesium chloride; the cerium salt is at least one of cerium nitrate, cerium acetate, and cerium chloride; the iron salt is at least one of iron nitrate, iron acetate, and iron chloride; the aluminum salt is at least one of aluminum nitrate, aluminum chloride, and aluminum acetate; the molar ratio of the magnesium salt, cerium salt, iron salt, and aluminum salt is 1:0.05 - 0.15:0.1 - 0.3:2 - 4.
[0029] Further, in step (1), the stirring time is 20 - 40 min, the alkali solution has a concentration of 1 - 3 mol / L, the alkali is sodium hydroxide and sodium carbonate, and the molar ratio of sodium hydroxide to sodium carbonate is 1:3.
[0030] Further, in step (1), the hydrothermal reaction conditions are to react at 130 - 170 °C for 6 - 14 h; the drying is to dry at 70 - 100 °C for 8 - 12 h.
[0031] Further, in step (2), the volume ratio of ethanol to water is 1:3; the ratio of MgAlCeFe-LDH, cobalt salt and dimethylimidazole is 10 g: 0.04 - 0.08 mol: 0.09 - 0.19 mol; the cobalt salt is at least one of cobalt nitrate, cobalt chloride and cobalt acetate.
[0032] Further, in step (2), the stirring time is 20 - 40 min; the drying is carried out at 70 - 90 °C for 10 - 20 h.
[0033] Further, in step (3), the mass ratio of ZIF-67@MgAlCeFe-LDH to fluorodecyltriethoxysilane is 1:0.1 - 0.3, and the drying is carried out at 70 - 90 °C for 10 - 20 h.
[0034] Based on the above-mentioned preparation method of a high-temperature resistant hydrophobic anti-corrosion coating, the preparation method includes the following steps: First, 2-benzothiazolethiosuccinic acid, hydrophobically modified ZIF-67@MgAlCeFe-LDH, water and ethanol are put into a high-speed mixer and mixed at a stirring rate of 3000 - 4000 r / min for 20 - 60 min. Then, epoxy resin, filler, dispersant, defoamer, film-forming aid and curing agent are added to the above mixture and stirred for another 15 - 35 min to obtain a coating. Then, the prepared coating is coated on a substrate material, left standing at room temperature for 24 - 30 h, and then cured at room temperature for 20 - 28 h to obtain a high-temperature resistant hydrophobic anti-corrosion coating after curing.
[0035] Based on the above-mentioned application of a high-temperature resistant hydrophobic anti-corrosion coating in the field of anti-corrosion.
[0036] The present invention has the following beneficial effects:
[0037] The present invention modifies MgAl-LDH hydrotalcite with Ce and Fe, and cooperates with in-situ loading of ZIF-67, which can significantly improve the corrosion resistance of the coating. Moreover, the corrosion resistance of the coating is further improved by 2-benzothiazolethiosuccinic acid. And hydrotalcite and ZIF-67 can significantly improve the high-temperature resistance. By adding hydrophobically modified ZIF-67@MgAlCeFe-LDH, the hydrophobic property of the coating can be improved. Thus, it can be seen that the high-temperature resistant hydrophobic anti-corrosion coating prepared by the present invention has excellent performance and good application prospects in the field of anti-corrosion. Specific Embodiments
[0038] The following specific examples are used to further illustrate the present invention, but the examples do not limit the present invention in any form. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the technical field.
[0039] The filler is nano-titanium dioxide with an average particle size of 50 nm; the dispersant is BYK163; the defoamer is BYK065; the film auxiliary agent is propylene glycol propyl ether; the curing agent is diethylenetriamine.
[0040] Unless otherwise specified, the reagents and materials used in the following examples are all commercially available.
[0041] Example 1
[0042] A high-temperature resistant hydrophobic anti-corrosion coating, by weight, the raw materials of the coating include the following components:
[0043] 120 parts of epoxy resin E44;
[0044] 5 parts of 2-benzothiazolylthiosuccinic acid;
[0045] 4 parts of hydrophobic modified ZIF-67@MgAlCeFe-LDH;
[0046] 6 parts of filler;
[0047] 4 parts of dispersant;
[0048] 2 parts of defoamer;
[0049] 3 parts of film auxiliary agent;
[0050] 25 parts of curing agent;
[0051] 25 parts of water;
[0052] 15 parts of ethanol.
[0053] The preparation method of the hydrophobic modified ZIF-67@MgAlCeFe-LDH includes the following steps:
[0054] (1) Weigh 1 mol of magnesium nitrate, 0.1 mol of cerium acetate, 0.2 mol of ferric chloride and 3 mol of aluminum nitrate, dissolve them in 150 mL of water to form a mixed salt solution, stir for 30 min, then add an alkali solution until the pH of the solution is 10. The alkali solution has a concentration of 2 mol / L, and the alkali is sodium hydroxide and sodium carbonate. The molar ratio of sodium hydroxide to sodium carbonate is 1:3. Then transfer it to a hydrothermal reaction kettle and react at 150 °C for 12 h. Centrifuge, wash, and dry at 90 °C for 10 h to obtain MgAlCeFe-LDH;
[0055] (2) Disperse 10 g of MgAlCeFe-LDH obtained in step (1) and 0.06 mol of cobalt nitrate into 150 mL of ethanol water, where the volume ratio of ethanol to water is 1:3. Stir for 30 min, then add 0.14 mol of dimethylimidazole, stir at 60 °C for 3 h, let it stand for 6 h, filter, wash, and dry at 80 °C for 16 h to obtain ZIF-67@MgAlCeFe-LDH;
[0056] (3) Disperse 10 g of ZIF-67@MgAlCeFe-LDH obtained in step (2) and 2 g of fluorodecyltriethoxysilane into 150 mL of ethanol by ultrasonic dispersion, stir at 65 °C for 3 h, filter, wash, and dry at 80 °C for 16 h to obtain hydrophobically modified ZIF-67@MgAlCeFe-LDH.
[0057] The preparation method of the high-temperature resistant hydrophobic anti-corrosion coating includes the following steps: First, put 2-benzothiazolylthiosuccinic acid, hydrophobically modified ZIF-67@MgAlCeFe-LDH, water and ethanol into a high-speed mixer and mix them at a stirring rate of 3500 r / min for 40 min. Then, add epoxy resin, filler, dispersant, defoamer, film-forming aid and curing agent to the above mixture and continue stirring for 25 min to obtain a coating. Then, coat the prepared coating on the steel, with a coating thickness of 4 mm, let it stand at room temperature for 26 h, and then cure at room temperature for 24 h to obtain a high-temperature resistant hydrophobic anti-corrosion coating after curing.
[0058] Example 2
[0059] A high-temperature resistant hydrophobic anti-corrosion coating, by weight, the raw materials of the coating include the following components:
[0060] 100 parts of epoxy resin E44;
[0061] 7 parts of 2-benzothiazolylthiosuccinic acid;
[0062] 2 parts of hydrophobically modified ZIF-67@MgAlCeFe-LDH;
[0063] 8 parts of filler;
[0064] 2 parts of dispersant;
[0065] 3 parts of defoamer;
[0066] 2 parts of film-forming aid;
[0067] 35 parts of curing agent;
[0068] 20 parts of water;
[0069] 20 parts of ethanol.
[0070] The preparation method of the hydrophobically modified ZIF-67@MgAlCeFe-LDH includes the following steps:
[0071] (1) Weigh 1 mol of magnesium chloride, 0.05 mol of cerium nitrate, 0.3 mol of iron acetate and 2 mol of aluminum acetate, dissolve them in 150 mL of water to form a mixed salt solution, stir for 20 min, then add alkali solution until the pH of the solution is 9. The alkali solution has a concentration of 1 mol / L, and the alkali is sodium hydroxide and sodium carbonate. The molar ratio of sodium hydroxide to sodium carbonate is 1:3. Then transfer it to a hydrothermal reaction kettle and react at 130 °C for 14 h. Centrifuge, wash, and dry at 70 °C for 12 h to obtain MgAlCeFe-LDH;
[0072] (2) Disperse 10 g of MgAlCeFe-LDH obtained in step (1) and 0.04 mol of cobalt chloride into 150 mL of ethanol-water, where the volume ratio of ethanol to water is 1:3. Stir for 20 min, then add 0.09 mol of dimethylimidazole, stir at 50 °C for 4 h, let it stand for 4 h, filter, wash, and dry at 70 °C for 20 h to obtain ZIF-67@MgAlCeFe-LDH;
[0073] (3) Ultrasonically disperse 10 g of ZIF-67@MgAlCeFe-LDH obtained in step (2) and 1 g of fluorodecyltriethoxysilane into 150 mL of ethanol, stir at 55 °C for 4 h, filter, wash, and dry at 70 °C for 20 h to obtain hydrophobically modified ZIF-67@MgAlCeFe-LDH.
[0074] The preparation method of the high-temperature resistant hydrophobic anti-corrosion coating is the same as the preparation process in Example 1.
[0075] Example 3
[0076] A high-temperature resistant hydrophobic anti-corrosion coating, by weight, the raw materials of the coating include the following components:
[0077] 140 parts of epoxy resin E44;
[0078] 3 parts of 2-benzothiazolylthiosuccinic acid;
[0079] 6 parts of hydrophobically modified ZIF-67@MgAlCeFe-LDH;
[0080] 4 parts of filler;
[0081] 6 parts of dispersant;
[0082] 1 part of defoamer;
[0083] 4 parts of film-forming aid;
[0084] 15 parts of curing agent;
[0085] 30 parts of water;
[0086] 10 parts of ethanol.
[0087] The preparation method of the hydrophobic modified ZIF-67@MgAlCeFe-LDH comprises the following steps:
[0088] (1) Weigh 1 mol of magnesium acetate, 0.15 mol of cerium chloride, 0.1 mol of iron nitrate and 4 mol of aluminum chloride, dissolve them in 150 mL of water to form a mixed salt solution, stir for 40 min, then add an alkali solution until the pH of the solution is 11. The alkali solution has a concentration of 3 mol / L, and the alkali is sodium hydroxide and sodium carbonate. The molar ratio of sodium hydroxide to sodium carbonate is 1:3. Then transfer it to a hydrothermal reaction kettle and react at 170 °C for 6 h. Centrifuge, wash, and dry at 100 °C for 8 h to obtain MgAlCeFe-LDH;
[0089] (2) Disperse 10 g of the MgAlCeFe-LDH obtained in step (1) and 0.08 mol of cobalt acetate into 150 mL of ethanol-water, where the volume ratio of ethanol to water is 1:3. Stir for 40 min, then add 0.19 mol of dimethylimidazole, stir at 70 °C for 2 h, let it stand for 8 h, filter, wash, and dry at 90 °C for 10 h to obtain ZIF-67@MgAlCeFe-LDH;
[0090] (3) Ultrasonically disperse 10 g of the ZIF-67@MgAlCeFe-LDH obtained in step (2) and 3 g of fluorodecyltriethoxysilane into 150 mL of ethanol, stir at 75 °C for 2 h, filter, wash, and dry at 90 °C for 10 h to obtain the hydrophobic modified ZIF-67@MgAlCeFe-LDH.
[0091] The preparation method of the high-temperature resistant hydrophobic anti-corrosion coating is the same as the preparation process in Example 1.
[0092] Comparative Example 1
[0093] Comparative Example 1 is basically the same as Example 1, except that: an equal amount of hydrophobic modified ZIF-67@MgAlFe-LDH is used to replace the hydrophobic modified ZIF-67@MgAlCeFe-LDH. The preparation method of the hydrophobic modified ZIF-67@MgAlFe-LDH comprises the following steps:
[0094] (1) Weigh 1 mol of magnesium nitrate, 0.3 mol of iron chloride and 3 mol of aluminum nitrate, dissolve them in 150 mL of water to form a mixed salt solution, stir for 30 min, then add an alkali solution until the pH of the solution is 10. The alkali solution has a concentration of 2 mol / L, and the alkali is sodium hydroxide and sodium carbonate. The molar ratio of sodium hydroxide to sodium carbonate is 1:3. Then transfer it to a hydrothermal reaction kettle and react at 150 °C for 12 h. Centrifuge, wash, and dry at 90 °C for 10 h to obtain MgAlFe-LDH;
[0095] (2) Disperse 10 g of the MgAlFe-LDH obtained in step (1) and 0.06 mol of cobalt nitrate into 150 mL of ethanol-water, where the volume ratio of ethanol to water is 1:3. Stir for 30 min, then add 0.14 mol of dimethylimidazole, stir at 60 °C for 3 h, let stand for 6 h, filter, wash, and dry at 80 °C for 16 h to obtain ZIF-67@MgAlFe-LDH;
[0096] (3) Ultrasonically disperse 10 g of the ZIF-67@MgAlFe-LDH obtained in step (2) and 2 g of fluorodecyltriethoxysilane into 150 mL of ethanol, stir at 65 °C for 3 h, filter, wash, and dry at 80 °C for 16 h to obtain hydrophobically modified ZIF-67@MgAlFe-LDH.
[0097] Comparative Example 2
[0098] Comparative Example 2 is basically the same as Example 1, except that: an equal amount of hydrophobically modified MgAlCeFe-LDH is used to replace hydrophobically modified ZIF-67@MgAlCeFe-LDH. The preparation method of the hydrophobically modified MgAlCeFe-LDH includes the following steps:
[0099] (1) Weigh 1 mol of magnesium nitrate, 0.1 mol of cerium acetate, 0.2 mol of ferric chloride, and 3 mol of aluminum nitrate, dissolve them in 150 mL of water to form a mixed salt solution, stir for 30 min, then dropwise add an alkali solution until the pH of the solution is 10. The alkali solution has a concentration of 2 mol / L, and the alkali is sodium hydroxide and sodium carbonate, and the molar ratio of sodium hydroxide to sodium carbonate is 1:3. Then transfer it to a hydrothermal reaction kettle and react at 150 °C for 12 h. Centrifuge, wash, and dry at 90 °C for 10 h to obtain MgAlCeFe-LDH;
[0100] (2) Ultrasonically disperse 10 g of the MgAlCeFe-LDH obtained in step (1) and 2 g of fluorodecyltriethoxysilane into 150 mL of ethanol, stir at 65 °C for 3 h, filter, wash, and dry at 80 °C for 16 h to obtain hydrophobically modified MgAlCeFe-LDH.
[0101] Comparative Example 3
[0102] Comparative Example 3 is basically the same as Example 1, except that: an equal amount of hydrophobically modified ZIF-67 is used to replace hydrophobically modified ZIF-67@MgAlCeFe-LDH. The preparation method of the hydrophobically modified ZIF-67 includes the following steps:
[0103] The preparation method of the hydrophobically modified ZIF-67 includes the following steps:
[0104] (2) Disperse 0.06 mol of cobalt nitrate into 150 mL of ethanol-water mixture, where the volume ratio of ethanol to water is 1:3. Stir for 30 min, then add 0.14 mol of dimethylimidazole, stir at 60 °C for 3 h, let stand for 6 h, filter, wash, and dry at 80 °C for 16 h to obtain ZIF-67;
[0105] (2) Ultrasonically disperse 10 g of ZIF-67 obtained in step (1) and 2 g of fluorodecyltriethoxysilane into 150 mL of ethanol, stir at 65 °C for 3 h, filter, wash, and dry at 80 °C for 16 h to obtain hydrophobically modified ZIF-67.
[0106] Comparative Example 4
[0107] Comparative Example 4 is basically the same as Example 1, except that an equal amount of 2-benzothiazolylthiosuccinic acid is used to replace the hydrophobically modified ZIF-67@MgAlCeFe-LDH.
[0108] Measure the water contact angles of the coatings prepared in Examples 1-3. The specific test results are shown in Table 1:
[0109] Table 1
[0110] Example 1 Example 2 Example 3 Water contact angle 125° 121° 124°
[0111] Measure the mechanical properties and corrosion resistance of Examples 1-3 and Comparative Examples 1-4. The specific test results are shown in Table 2: The test standards are as follows:
[0112] Adhesion (pull-off adhesion): GB / T5210;
[0113] Corrosion protection performance: GB / T 9274-88 and GB / T 1771-91.
[0114]
[0115] It can be seen from Table 2 that the anti-corrosion coating prepared by the present invention has excellent mechanical properties and corrosion resistance.
[0116] Test the dry heat resistance of the anti-corrosion coatings of Examples 1-3 according to the test method ASTM D 5499 Method A. There are no defects in Examples 1-3 at 200 °C. It can be seen that the anti-corrosion coating prepared by the present invention has high temperature resistance.
[0117] The above embodiments are the preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement methods and are all included in the protection scope of the present invention.
Claims
1. A high-temperature resistant hydrophobic anti-corrosion coating, characterized in that: By weight parts, the raw materials of the coating include the following components: 100 - 140 parts of epoxy resin; 3 - 7 parts of 2 - benzothiazolethiosuccinic acid; 2 - 6 parts of hydrophobic modified ZIF - 67@MgAlCeFe - LDH; 4 - 8 parts of filler; 2 - 6 parts of dispersant; 1 - 3 parts of defoamer; 2 - 4 parts of film - forming aid; 15 - 35 parts of curing agent; 20 - 30 parts of water; 10 - 20 parts of ethanol.
2. The high-temperature resistant hydrophobic anti-corrosion coating according to claim 1, wherein: The preparation method of the hydrophobic modified ZIF - 67@MgAlCeFe - LDH includes the following steps: (1) Weigh magnesium salt, cerium salt, iron salt and aluminum salt, dissolve them in water to form a mixed salt solution, stir, then dropwise add alkali solution until the pH of the solution is 9 - 11, then transfer it to a hydrothermal reaction kettle for hydrothermal reaction, centrifuge, wash, and dry to obtain MgAlCeFe - LDH; (2) Disperse the MgAlCeFe - LDH obtained in step (1) and cobalt salt into ethanol - water, stir, then add dimethylimidazole, stir at 50 - 70 °C for 2 - 4 h, let it stand for 4 - 8 h, filter, wash, and dry to obtain ZIF - 67@MgAlCeFe - LDH; (3) Ultrasonically disperse the ZIF - 67@MgAlCeFe - LDH obtained in step (2) and fluorodecyltriethoxysilane into ethanol, stir at 55 - 75 °C for 2 - 4 h, filter, wash, and dry to obtain the hydrophobic modified ZIF - 67@MgAlCeFe - LDH.
3. The high-temperature resistant hydrophobic and anti-corrosion coating according to claim 2, wherein: In step (1), the magnesium salt is at least one of magnesium nitrate, magnesium acetate, and magnesium chloride; the cerium salt is at least one of cerium nitrate, cerium acetate, and cerium chloride; the iron salt is at least one of iron nitrate, iron acetate, and iron chloride; the aluminum salt is at least one of aluminum nitrate, aluminum chloride, and aluminum acetate; the molar ratio of the magnesium salt, cerium salt, iron salt, and aluminum salt is 1:0.05 - 0.15:0.1 - 0.3:2 - 4.
4. A high-temperature resistant hydrophobic anti-corrosion coating according to claim 2, characterized in that: In step (1), the stirring time is 20 - 40 min, the alkali solution has a concentration of 1 - 3 mol / L, the alkali is sodium hydroxide and sodium carbonate, and the molar ratio of sodium hydroxide to sodium carbonate is 1:
3.
5. The high-temperature resistant hydrophobic and anti-corrosion coating according to claim 2, characterized in that: In step (1), the hydrothermal reaction conditions are reacting at 130 - 170 °C for 6 - 14 h; the drying is drying at 70 - 100 °C for 8 - 12 h.
6. The high-temperature resistant hydrophobic anti-corrosion coating according to claim 2, wherein: In step (2), the volume ratio of ethanol to water is 1:3; the ratio of MgAlCeFe - LDH, cobalt salt, and dimethylimidazole is 10 g:0.04 - 0.08 mol:0.09 - 0.19 mol; the cobalt salt is at least one of cobalt nitrate, cobalt chloride, and cobalt acetate.
7. A high-temperature resistant hydrophobic anti-corrosion coating according to claim 2, characterized in that: In step (2), the stirring time is 20 - 40 min; the drying is drying at 70 - 90 °C for 10 - 20 h.
8. The high-temperature resistant hydrophobic anti-corrosion coating according to claim 2, characterized in that: In step (3), the mass ratio of ZIF - 67@MgAlCeFe - LDH to fluorodecyltriethoxysilane is 1:0.1 - 0.3, and the drying is drying at 70 - 90 °C for 10 - 20 h.
9. The preparation method of a high-temperature resistant hydrophobic anti-corrosion coating according to any one of claims 1-8, characterized in that: The preparation method comprises the following steps: First, 2-benzothiazole thiosuccinic acid, hydrophobic modified ZIF-67@MgAlCeFe-LDH, water and ethanol are put into a high-speed blender for mixing, the stirring rate is 3000-4000 r / min, and stirring is carried out for 20-60 min. Then, epoxy resin, filler, dispersant, defoamer, film auxiliary and curing agent are added to the above mixture and stirring is continued for 15-35 min to obtain a coating. Then, the prepared coating is coated on a substrate material, left standing at room temperature for 24-30 h, and then cured at room temperature for 20-28 h to obtain a high-temperature resistant hydrophobic anti-corrosion coating after curing.
10. Application of a high-temperature resistant hydrophobic anti-corrosion coating according to any one of claims 1-8 in the field of anti-corrosion.
Citation Information
Patent Citations
Hydrophobic modified anticorrosive coating and preparation method thereof
CN118165613A
Self-repairing organic coating applied to gathering pipeline and preparation method of self-repairing organic coating
CN103360907A
Self-repairing anticorrosive coating and preparation method thereof
CN111205745A
Preparation method of high-corrosion-resistance modified epoxy resin composite coating
CN112341900A
NiFe-LDH / Co-CNTs nano composite material and preparation method and application thereof
CN113113615A
Cited By
Protective coating for aluminum alloy heat exchange tube and preparation method of protective coating
CN120775469A
Protective coating for aluminum alloy heat exchange tubes and method for producing same
CN120775469B